Currícuo e prática pedagógica da Educação Física (Universidade Federal de Goiás, 2006)
O artigo em questão trata de temas que hoje integram as discussões sobre Educação Física, como currículo e prática pedagógica, numa dimensão mais política e mais pedagógica. Trata também da própria identidade deste campo do conhecimento, além de outros temas que o rodeiam: educação, ensino, professor, escola. Projeta ainda, futuros embates que certamente terão influência nas estruturas da Educação Física. This article deals with subjects currently integrated in the discussion about Physical Education, such as the curriculum and the pedagogical practice in a more political and pedagogical dimension. It also deals with the identity of this field of knowledge, beside other subjects related to it, such as education, teaching, teacher and school. In addition, it foresees future shocks which will certainly have influence upon the structure of Physical Education.